The Role of Sense of Place in Enhancing Environmental Sustainability: A Case Study of the Waterfront in Jinan, China - Nor Haslina Ja’afar,; Ziyi Hana,; Alice Sabrina Ismail,; Elina Mohd Husini, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Urban waterfronts are increasingly recognized for their potential to integrate environmental, social, and cultural values, making them essential for sustainable development. While many studies have focused on technical solutions to improve sustainability, few have addressed the significance of the sense of place in fostering environmental stewardship in waterfront areas. This research aims to explore how the sense of place, encompassing cognitive, affective, and behavioral aspects, contributes to environmental sustainability in urban waterfronts. A mixedmethods approach was adopted. Quantitative data were collected through a convenience sampling questionnaire survey of waterfront users (n = 326) to identify significant indicators of the sense of place. Additionally, qualitative insights were obtained from semi-structured interviews with 12 frequent waterfront users to understand how the meanings associated with a place influence sustainable behaviors. The results highlight eight crucial factors that strengthen the sense of place and promote environmental sustainability: 1) attractive landmarks or focal points, 2) regional characteristics that create narrative landscapes, 3) well-maintained surroundings, 4) community events, 5) welcoming public spaces, 6) conservation of cultural and historical heritage, 7) participatory activities, and 8) informative signboards. This study provides urban designers, waterfront developers, and policymakers with a theoretical framework for developing urban waterfronts that enhance community attachment and encourage sustainable practices. It also delivers valuable insights for promoting sustainability in underdeveloped or rural waterfront regions.